American Nightingale the story of Frances Slanger, forgotten heroine of Normandy - Welch, Bob (Atria Books, 2004)
Traces the life of an American nurse who died at Normandy, describing her childhood in Poland, immigration to America, decision to become a nurse, and letter to the Stars and Stripes newspaper that would inspire thousands of soldiers.